Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1101/gad.1320505
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic molecular linkers of the genome: the first decade of SMC proteins

Abstract: Structural maintenance of chromosomes (SMC) proteins are chromosomal ATPases, highly conserved from bacteria to humans, that play fundamental roles in many aspects of higher-order chromosome organization and dynamics. In eukaryotes, SMC1 and SMC3 act as the core of the cohesin complexes that mediate sister chromatid cohesion, whereas SMC2 and SMC4 function as the core of the condensin complexes that are essential for chromosome assembly and segregation. Another complex containing SMC5 and SMC6 is implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
313
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(322 citation statements)
references
References 179 publications
(224 reference statements)
5
313
0
4
Order By: Relevance
“…Second, the uncovered degree of flexibility in the chromosomal location requirements for condensin binding may indicate that the fixed chromosomal position of these sites is not essential for overall chromosome condensation. This is consistent with the in vitro assay (Hirano, 2004;Losada and Hirano, 2005) showing that topological changes introduced into DNA molecule locally (at the condensin binding site) are then translated (via compensatory supercoiling) into whole-molecule topological changes. Third, the substantial relief of the essential condensin function in the segregation of rDNA (Wang et al, 2006) and the discovered here formation of an altered binding pattern across chromosomes, yet more reproducible and robust than in wild type, both make ErDNA cells an attractive experimental model with better approximation for condensin biology in higher eukaryotes.…”
Section: Discussionsupporting
confidence: 88%
“…Second, the uncovered degree of flexibility in the chromosomal location requirements for condensin binding may indicate that the fixed chromosomal position of these sites is not essential for overall chromosome condensation. This is consistent with the in vitro assay (Hirano, 2004;Losada and Hirano, 2005) showing that topological changes introduced into DNA molecule locally (at the condensin binding site) are then translated (via compensatory supercoiling) into whole-molecule topological changes. Third, the substantial relief of the essential condensin function in the segregation of rDNA (Wang et al, 2006) and the discovered here formation of an altered binding pattern across chromosomes, yet more reproducible and robust than in wild type, both make ErDNA cells an attractive experimental model with better approximation for condensin biology in higher eukaryotes.…”
Section: Discussionsupporting
confidence: 88%
“…SMC proteins are ABC-like ATPases, which typically associate with chromatin and contain a central coiled-coil and a dimerisation region. Examples of SMC heterodimers complexes include SMC1/SMC3 (cohesin) and SMC2/SMC4 (condensin), which are essential in sister chromatid attachment and chromosome assembly/segregation respectively (Losada and Hirano, 2005;Haering, and Nasmyth. 2003;.…”
Section: Screening Candidate Centrosomal Protein Xcep63 Regulates Spmentioning
confidence: 99%
“…Although the main role of the Smc5-Smc6 complex is still unclear, recent studies have shown that this complex is recruited to the induced DNA double-strand-breaks (DSBs) [31,32] to enhance their repair by sister-chromatid recombination [31,32]. Smc5-6 heterodimer makes a multi-protein complex with six additional subunits in budding yeast (Nse1-6) [28]. Nse2 also known as Mms21 is an E3 SUMO ligase and several studies suggested that Mms21 links Smc5-6 to DNA repair role through sumoylation [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Eukaryotic cells have three protein complexes containing chromosomal ATPases of the Structural Maintenance of Chromosomes (SMC) family that function in various aspects of chromosome metabolism [26][27][28][29]. SMC complexes are characterized by the presence of a heterodimer of Smc proteins at the core with additional non-Smc subunits.…”
Section: Introductionmentioning
confidence: 99%